Exploring Student Experiences with the "FunNy-Fun&Handy" Android Listening App: A Study on Enhancing English Listening Skills through Popular Culture Integration - Nasution, Nazlah Syahaf; Kifli, Barli (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
This research investigates the impact of an Android-based listening app, "FunNy-Fun&Handy," on enhancing students' English listening skills through engaging content on popular culture topics. Descriptive Qualitative method used in this research. Eleven participants engaged with the app, and their experiences were assessed through a Google Form questionnaire. Responses highlighted positive perceptions of the app's impact on motivation (Mean = 4.45), user interface (Mean = 4.18), and content effectiveness (Mean = 4.27). Participants expressed satisfaction with the app's usability (Mean = 4.27) and intention to continue using it (Mean = 4.45). Qualitative insights emphasized the engaging content's value, while suggestions for a balanced blend of entertainment and academics were noted. This study's findings underscore the app's potential for enhancing motivation and skill development, contributing to language learning applications. The research sheds light on the integration of popular culture content within language learning contexts, offering a promising avenue for improving students' English listening skills.